Representasi Bahasa pada Anak Usia Dini Penderita Keterlambatan Berbicara (Speech Delay) di SLB Negeri 1 Makassar - Intan Mutiara Safira; Sultan Sultan; Baharman Baharman (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
This study aims to describe the representation of vocabulary and sentences in early childhood with speech delay at SLB Negeri 1 Makassar. The type of research used is qualitative research with a focus on language representation. The study used a qualitative method with a descriptive design, involving three main subjects aged 6 years as data sources. Data was collected through observation and documentation of children's speech, then analyzed descriptively through data reduction, data presentation, and conclusion drawn, with the validity of the data tested using triangulation of sources, methods, and theories. The results of the study showed that children were able to use various basic vocabulary including nouns, verbs, adjectives, adverbs, pronouns, numeralia, prepositions, conjunctions, and interjections, although pronunciation was still often inaccurate. Children also produce simple sentences in the form of declaratives, interrogatives, and imperatives that function in daily communication. This study confirms that children with speech delay can still convey meaning through simple language structures, and the support of the learning environment, teachers, and parents plays an important role in facilitating their language development. These findings are expected to be a reference in the development of language stimulation strategies for children with special needs.